DEVELOPING AN EFFICIENT AIR PURIFICATION SYSTEM: FOCUS ON AIRBORNE DISEASE AND ALLERGEN CONTROL - Ali Samir A.; Hasan Jumaah Mrayeh; Salih Meri Al-Absi; Gabriella Bognar Vadászné; Alaa Alrudhan Abed (Journal of Mechanics of Continua and Mathematical Sciences, 2025)
The objective of this paper was to design an air purifier system to solve the relevant problem of airborne disease and allergen spread in classrooms and retail settings. While reducing the risk of COVID exposure through airborne particles was the main objective of the system, reducing the risk of Influenza, and the concentration of common allergens such as dust and pollen were also central to the design. The implementation involved a portable air purification system that was affordable and a size appropriate for classrooms and small businesses. The design was tested using CAD designs and various component specifications. These specifications were as follows; filtration ability, airflow capacity, floor space used, noise level, the time before UV decay took place, price of both a prototype and final market design, weight, and time before maintenance was required. This design met all main requirements, excluding the noise level, which was found to be 10% higher than required in the engineering specification. However, this was overruled by the need to reduce costs and increase power. Future recommendations and next steps include adding more advanced electrical control components, considering the effectiveness of UVC light specifically against COVID-19, soundproofing the design, and other minor changes to improve the system.